Prolonged Leptospira Urinary Shedding in a 10-Year-Old Girl. (25th March 2012) - Chow, Emilie; Deville, Jaime; Nally, Jarlath; Lovett, Michael; Nielsen-Saines, Karin
Abstract : We present a case of leptospirosis in a previously healthy girl following a trip to Costa Rica. While she was clinically asymptomatic, she had spirochetes cultured from her urine six weeks following her trip. Prolonged urinary shedding following infection with Leptospira is possible in humans and often has subtle manifestations in children.